1991
DOI: 10.1016/0960-1686(91)90280-k
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric concentrations and temporal variations of C1C3 carbonyl compounds at two rural sites in central Ontario

Abstract: AIIIttact-Measurements of formaldehyde, acetaldehyde, acetone and propionaldehyde concentrations were made at two rural sites in central Ontario. One site (at Egbert, Ont.) is located~60 km northwest of Toronto, while the other site Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(86 citation statements)
references
References 30 publications
4
76
1
5
Order By: Relevance
“…The levels of atmospheric carbonyls measured in different areas are listed in Table 5 Canada reported by Shepson et al (1991) and in a background site of UST, Hong Kong reported by Cheng et al (2014), but significantly lower than those reported in urban areas in the world (Pang and Mu 2006;Feng et al 2005;Moussa et al 2006;Kalabokas et al 1988;Possanzini et al 1996).…”
Section: Comparison With Other Citiesmentioning
confidence: 91%
See 4 more Smart Citations
“…The levels of atmospheric carbonyls measured in different areas are listed in Table 5 Canada reported by Shepson et al (1991) and in a background site of UST, Hong Kong reported by Cheng et al (2014), but significantly lower than those reported in urban areas in the world (Pang and Mu 2006;Feng et al 2005;Moussa et al 2006;Kalabokas et al 1988;Possanzini et al 1996).…”
Section: Comparison With Other Citiesmentioning
confidence: 91%
“…The ratio of formaldehyde/acetaldehyde (C1/C2) has been widely used as an indicator of a biogenic source for formaldehyde (Shepson et al 1991). C1/C2 ratios were reported to vary from about 1 in urban areas (Ho et al 2002;Feng et al 2005;Pang and Mu 2006;Xu et al 2010) to about 10 in deciduous forests (Jacob and Wofsy 1988;Shepson et al 1991).…”
Section: Ratios Of Formaldehyde/acetaldehydementioning
confidence: 99%
See 3 more Smart Citations